Metro Manila visions no. 1-9 - San Juan, Epifanio, Jr.; Philippines Cultural Studies Center (Storrs, Conn. Philippines Cultural Studies Center, 2010)
Epifanio San Juan, Jr.'s travel video compilation of UP Diliman and Metro Manila landmarks, places, streets, events, current news and Gloria Resign rallies between 2008 to 2010. Each video clip was shown without narration or description.
Vision no. 1. [Commonwealth Ave., Philcoa, Quaipo Nazareno parade] (9 min., 52 sec.) -- vision no. 2. Before the flood : Marikina, Rizal at the atelier, Grace & Abdulmari Imao residence (9 min., 55 sec.) -- vision no. 3. [UP Diliman academic oval, UP Diliman Churches, UP Main Library and nearby kiosk, Vinzons Hall student's tambayan, StandUP students' rally] (9 min., 55 sec.) -- vision no. 4. [Rockwell Mall, Makati, The Fort Global City, Market Market Mall, Katrina Halili and Hayden Kho video, SM Megamall facade, New Year baby news] (9 min., 53 sec.) -- vision no. 5. [UP Diliman student rally at Palma Hall, Gloria Resign Rally in front of the Manila Post Office] (23 min., 13 sec.) -- vision no. 6. [UP Diliman Quezon Hall, UP Diliman outdoor statues] (9 min., 55 sec.) -- vision no. 7. [Makati Gloria Resign rally] (9 min., 57 sec.) -- vision no. 8. [Newspaper headlines, UP, TV Patrol news, Jeepney at Philcoa, Quiapo Nazareno Parade, National Housing Authority Backside view, Tricycle terminal] (9 min., 53 sec.) -- vision no. 9. [Taal Volcano overlooking, seminary tour, farm] (9 min., 57 sec.)
DVD.
Keywords: University of the Philippines Diliman; Demonstrations -- Philippines; Philippines -- Social conditions; Visual anthropology